Astronomer, Cartographer and Naturalist of the New World The Life and Scholarly Achievements of Georg Marggrafe (1610-1643) in Colonial Dutch Brazil. Volume 2 - Zuidervaart, Huib J.; Matsuura, Oscar T. (Studies in the History of Knowledge, 2022)
Georg Marggrafe, Colonial Dutch Brazil, Early Modern Science, Astronomy, 17th century